STREOTYPE OF PUBLIC RELATIONS PROFESSION IN JAKARTA - Dio Herman Saputro; Satya Candrasari; Ovi Olivia Belida (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2017)
Public Relations is known as a female profession, concerned physical, and suitable for women. The purpose of this research is to analyze Public Relations stereotype as a woman profession, concerned with physical, and feminine. This research is examined though face to face in-depth interview method with 10 Public Relations practitioners from variety industry in Jakarta. Findings showed that Public Relations stereotype is not necessarily a pretty woman, physically attractive, and majority men still dabble as Public Relations practitioners in the field of industry. Nevertheless, it cannot be denied that women still dominant in a Public Relations profession. The society's view that the face of PR is a woman show there is a miss perception of PR term itself caused by lack of understanding of PR literacy as management function, not a women profession, equal to actress celebrity's job, and oriented physical. The Negative stereotype about PR profession in Jakarta caused this profession is not as appreciated as a doctor or accountant profession.